Exploring the influence of pregnancy on cognitive function in women: a systematic review - Jana Younis; Malak Bleibel; Jad El Masri; Ali Ismail; Linda Abou‑Abbas (BMC Pregnancy and Childbirth)
Abstract Background Pregnancy has been increasingly recognized for its potential impact on cognitive function influenced significantly by hormonal fluctuations such as estrogen and progesterone. However, the findings from research in this area remain debated, often varying with individual factors and pregnancy trimesters. Objective This study aims to systematically review existing literature and empirical research to better understand the phenomenon known as “pregnancy brain” and its association with cognitive change. Methods We conducted a systematic review of peer-reviewed English language articles sourced from Medline, Cochrane Library, and PubMed. Using search terms (pregnancy OR pregnant) AND (cognit* OR memory OR cognitive function*), we identified relevant articles published from the inception of these databases to July 2023. Due to the diverse outcomes in identified studies, a meta-analysis was not feasible, and therefore, a narrative synthesis was conducted to summarize findings. Results Screening 3892 studies yielded 31 that met inclusion criteria, encompassing 1596 pregnant women and 1450 non-pregnant controls. Notably, seven studies originated from Australia, of which four were rated as low quality. The aggregated findings suggest that pregnancy modestly affects verbal memory and attention compared to non-pregnant controls, with indications that this decline persists postnatally. Conclusion Future efforts should prioritize uncovering the underlying mechanisms driving these cognitive changes during pregnancy and consider developing targeted interventions. Such initiatives aim to mitigate potential impacts on maternal well-being, advocating for comprehensive support systems tailored to pregnant individuals navigating cognitive shifts during this transformative period.